(untitled) (Archives of Clinical and Medical Case Reports, 2019)
From 1990 to 2015, maternal mortality has decline by 43.9 per cent worldwide. In sub-Saharan Africa countries including Togo, it’s still a great concern. Sustainable Development Goals recommend to achieve a maternal mortality ratio of less than 70 maternal deaths per 100,000 live births by 2030. We report a case of maternal death of a Christian pregnant woman that occurred in Haho health district in 2018. Data were collected through a review of registers, medical and antenatal records and verbal autopsy. The deceased suffered of severe pre-eclampsia like during her two previous pregnancies that ended with two stillbirths, but this time around she could not survive it despite the six antenatal visits with a gynaeco-obstetrician. Actually, she had the strong believe that the two stillbirths was uncommon and a result of a spell cast on her, and that only her faith through prayers could deliver her. Therefore, she did not comply with her reference to a hospital with a surgical service for a cesarean delivery. Her death was preventable. There is a need to strengthen patients’ therapeutic education and communication around diseases especially during pregnancies in order to help them know what faith cannot help achieve.